Analysis of Errors in Resolving FPB and KPK Story Questions Based on Polya Procedures for Class IV Elementary School Students - Utami, Gayatri; Saputro, Bagus Ardi; Asri Untari, Mei Fita (Universitas Pendidikan Ganesha, 2020)
This research was conducted based on the existing problems, namely the student’s lack of ability when solving math story questions about FPB and KPK material. This study aims to analyze the types of student’s mistake in solving the FPB and KPK material story questions. In addtion, it also aims to describe the possible causes of errors made by IV grade elementary school students in solving FPB and KPK story questions based on Polya’s completion steps. The completion of a story based problem consists of four stages, namely understanding the problem, compiling a plan, implementing the plan, and re-checking the solution obtained. The research uses a qualitative approach with descriptive research. The method use is the method of testing and documentation. The results of the study show that there are four types of errors of grade IV elementary school students in solving the FPB dan KPK material story questions based on Polya’s solving steps, namely errors in undestanding the questions, errors ini planning, errors in imolementing the plans, and errors in checking the solutions obtained. The possibility of students making mistake in solving story problems is due to internal factors (within the students themselves), including haste and inaccuracy of students in the process.